Approaches To The Study Of Religion And Medicine In Scientific Research - Alidjanova Lazizakhon Abbasovna (Genius Journals, 2022)
The importance of medicine has never waned throughout human history. The question of whether it was based on religion or violated religious precepts was particularly hotly debated. Although the medical works published by ancient scholars have no religious motivation, the topic of medicine has always been explained in religious literature. Later, as religion's influence in society grew, medical scientists attempted to prove their points through religion. At the same time, the monks were also practicing medicine. This is demonstrated in Christianity through Jesus' (pbuh) miracles, such as the healing of the blind, the mending of the blind's eyes, the washing of the lepers, and the healing of the paralyzed. Following Jesus' (a.s) ascension from the earth, the apostles took on the work, followed by the saints. After all, the ailment is caused by sin, and the only way to heal it is via repentance and spiritual purity, according to Christian teaching. As a result, the issues of religion, source, and medicine have occupied a unique position throughout history
Keywords: Medicine; religion; research; West